Social Identities as Pathways into and out of Addiction - Dingle, Genevieve A.; Cruwys, Tegan; Frings, Daniel (Frontiers in Psychology, 2015)
There exists a predominant identity loss and “redemption” narrative in the addiction literature describing how individuals move from a “substance user” identity to a “recovery” identity. However, other identity related pathways influencing onset, treatment seeking and recovery may exist, and the process through which social identities unrelated to substance use change over time is not well understood. This study was designed to provide a richer understanding of such social identities processes. Semi-structured interviews were conducted with 21 adults residing in a drug and alcohol therapeutic community (TC) and thematic analysis revealed two distinct identity-related pathways leading into and out of addiction. Some individuals experienced a loss of valued identities during addiction onset that were later renewed during recovery (consistent with the existing redemption narrative). However, a distinct identity gain pathway emerged for socially isolated individuals, who described the onset of their addiction in terms of a new valued social identity. Almost all participants described their TC experience in terms of belonging to a recovery community. Participants on the identity loss pathway aimed to renew their pre-addiction identities after treatment while those on the identity gain pathway aimed to build aspirational new identities involving study, work, or family roles. These findings help to explain how social factors are implicated in the course of addiction, and may act as either motivations for or barriers to recovery. The qualitative analysis yielded a testable model for future research in other samples and settings.